A synthesis of carbon dioxide and methane dynamics during the ice‐covered period of northern lakes. Issue 3 (11th April 2018) - Denfeld, Blaize A.; Baulch, Helen M.; del Giorgio, Paul A.; Hampton, Stephanie E.; Karlsson, Jan
Abstract: The ice‐covered period on lakes in the northern hemisphere has often been neglected or assumed to have less importance relative to the open water season. However, recent studies challenge this convention, suggesting that the winter period is more dynamic than previously thought. In this review, we synthesize the current understanding of under‐ice carbon dioxide (CO2 ) and methane (CH4 ) dynamics, highlighting the annual importance of CO2 and CH4 emissions from lakes at ice‐melt. We compiled data from 25 studies that showed that the ice‐melt period represents 17% and 27% of the annual CO2 and CH4 emissions, respectively. We also found evidence that the magnitude and type of emission (i.e., CO2 and CH4 ) varies with characteristics of lakes including geographic location, lake morphometry, and physicochemical conditions. The scarcity of winter and spring carbon data from northern lakes represents a major gap in our understanding of annual budgets in these lakes and calls for future research during this key period.